Radiofrequency ablation versus stripping of great saphenous vein in the management of varicose veins - Tyagi, Vikas; Chopra, Saumya; Ahmad, Samir; Sudhir Kumar Jain; Amrita Dua (Asian Journal of Medical Sciences, 2024)
Background: Varicose veins are defined as dilated, tortuous subdermal veins >3 mm in diameter. It is a common entity affecting an estimated 10% of population. Aims and Objectives: The aim was to compare the efficacy of radiofrequency ablation (RFA) with great saphenous vein (GSV) stripping in patients with lower limb varicose veins in terms of disappearance of visible varicosities. Materials and Methods: It was a prospective randomized controlled study, conducted in a tertiary care medical college with the study population consisting of patients suffering from varicose veins. Totally 30 patients were enrolled and divided into 2 groups of 15 patients each. Group A underwent RFA while Group B underwent stripping of GSV with flush ligation of saphenofemoral junction. Results: The mean duration of the procedure in Group A was 53.67±6.6 min while in Group B it was 101.4±11.85 min which was statistically significant (P<0.0001). The mean duration of return to routine activities and work was 2.2±0.41 days in Group A and 3.07±1.16 days in Group B which was statistically significant (P=0.024). Post-operative analgesic requirement was similar in both groups (P=0.224). Complete remission was observed in all patients at 12 months visit and there was no recurrence identified even after a follow-up period of 4 years. Conclusion: RFA was found to be as effective as stripping of GSV in terms of obliteration of veins. The duration of procedure was found to be much less in RFA. Furthermore, cosmetic results, ulcer healing and patient satisfaction rate was better in RFA group. Patient return to normal activity was significantly earlier in RFA group.